Advanced bioactive glue tethering Lubricin/PRG4 to promote integrated healing of avascular meniscus tears - Solaiman Tarafder; Jaskirti Ghataure; David Langford; Rachel Brooke; Ryunhyung Kim; Samantha Lewis Eyen; Julian Bensadoun; Jeffrey T. Felix; James L. Cook; Chang H. Lee (Bioactive Materials, 2023)
Meniscus injuries are extremely common with approximately one million patients undergoing surgical treatment annually in the U.S. alone, but no regenerative therapy exist. Previously, we showed that controlled applications of connective tissue growth factor (CTGF) and transforming growth factor beta 3 (TGFβ3) via fibrin-based bio-glue facilitate meniscus healing by inducing recruitment and stepwise differentiation of synovial mesenchymal stem/progenitor cells. Here, we first explored the potential of genipin, a natural crosslinker, to enhance fibrin-based glue's mechanical and degradation properties. In parallel, we identified the harmful effects of lubricin on meniscus healing and investigated the mechanism of lubricin deposition on the injured meniscus surface. We found that the pre-deposition of hyaluronic acid (HA) on the torn meniscus surface mediates lubricin deposition. Then we implemented chemical modifications with heparin conjugation and CD44 on our bioactive glue to achieve strong initial bonding and integration of lubricin pre-coated meniscal tissues. Our data suggested that heparin conjugation significantly enhances lubricin-coated meniscal tissues. Similarly, CD44, exhibiting a strong binding affinity to lubricin and hyaluronic acid (HA), further improved the integrated healing of HA/lubricin pre-coated meniscus injuries. These findings may represent an important foundation for developing a translational bio-active glue guiding the regenerative healing of meniscus injuries.